-2p=-10+3p

Simple and best practice solution for -2p=-10+3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2p=-10+3p equation:



-2p=-10+3p
We move all terms to the left:
-2p-(-10+3p)=0
We add all the numbers together, and all the variables
-2p-(3p-10)=0
We get rid of parentheses
-2p-3p+10=0
We add all the numbers together, and all the variables
-5p+10=0
We move all terms containing p to the left, all other terms to the right
-5p=-10
p=-10/-5
p=+2

See similar equations:

|   250=2.5z= | | 5-4(2-x=17 | | 17/30=n/300 | | j/2-1.1=1.9 | | 100-10x+2-7x=180 | | 8b²-7=193 | | -3c-2=-4c-7 | | 2-7x+100-10x=180 | | 1/100=n/6 | | x-36+1/2x+18+3x-72=180 | | 6x+4x+8=90 | | 54=9x8x | | 3f=10+5f | | 28x-6=-6 | | 7+y=12=7+y | | .76m+2=3 | | 6+3q=15.9 | | 10-m=-3m | | 5.9–m=-4.5–5m | | 5–4(2–x)=17 | | 9z-10=7z | | 5–4(2–x)=18 | | -7p+9=-10p | | x=8/3=8 | | .76m+2=-3 | | 7x-2=3x+9= | | 2-7x+100-10x=86-21x | | -8x=-6x+1 | | 3x+211=3x+2 | | T(t)=3t/t^2+1 | | -x+4(7+4x)=-3(-5+-5x) | | 80/100=x/32 |

Equations solver categories